Feasibility of 6-month maintenance cetuximab after adjuvant concurrent chemoradiation plus cetuximab in squamous cell carcinoma of the head and neck - Matuschek, Christiane; Bölke, E.; Belka, C.; Ganswindt, U.; Henke, M.; Stegmaier, P.; Bamberg, M.; Welz, S.; Debus, Jürgen; Gioules, Alexandros; Voigt, A.; Volk, G.; et al. (Strahlentherapie und Onkologie, 2013)
Close resection margins < 5 mm (CM) or extra capsular extent at the lymph nodes (ECE) impair the prognosis of patients with squamous cell cancer of the head and neck (SCCHN) scheduled for adjuvant radiochemotherapy. We conducted a multicenter phase II study to investigate toxicity and efficacy of additional cetuximab administered concomitantly and as maintenance for the duration of 6 months following adjuvant radiochemotherapy., Ppreliminary results on feasibility and acute toxicity on skin and mucosa are presented in this article.